AB0646 Low Reactive Hyperemia Index Assessed by Endopat and High Circulating Level of Placenta Growth Factor, Growth Differentiation Factor-15 and Pentraxin-3 Reflect the Presence of Vasculopathy as Well as Progressive Disease Status in Patients with Systemic Sc. (10th June 2014) - Kawashiri, S.-Y.; Nishino, A.; Nakashima, Y.; Suzuki, T.; Horai, Y.; Nakashima, M.; Mizokami, A.; Matsuoka, N.; Iwamoto, N.; Ichinose, K.; Arima, K.; Tamai, M.; et al.
Abstract : Background: Vasculopathy and progressive disease status such as digital ulcer, pulmonary arterial hypertension and interstitial lung disease (ILD) deteriorate the quality of life as well as survival rate in patients with systemic sclerosis (SSc). Angiogenesis and fibrotic process appear to be dysregulated in patients with SSc. Objectives: We have explored the surrogate indices to reflect vascular damage and disease progression in patients with SSc using reactive hyperemia index assessed by EndoPAT and circulating biomarkers. Methods: Fifty-two patients with SSc (limited type; 40 patients, diffuse type; 12 patients) were enrolled. All the patients gave their informed consent to be subjected to the protocol that was approved by the Institutional Review Board of Nagasaki University. They were examined by Chest X-ray or CT, echocardiography, respiratory function test, blood test including autoantibodies and NT-proBNP, endothelial function test by EndoPAT (RHI; Reactive Hyperemia Index), skin assessment by modified Rodonan Skin Score (mRSS) at the same day. Serum levels of placenta growth factor (PlGF) and vascular endothelial growth factor (VEGF) and plasma levels of growth differentiation factor (GDF)-15 and pentraxin (PTX)-3 were measured by ELISA. Results: The mean of age was 61.5 y.o. and that of disease duration was 5.2 years. Twenty patients complicated with ILD, 4 patients with pulmonary hypertension including border line, and 9 patients with digital ulcer. Anti-Tpo-1 antibodies were positive in 10 patients, anti-centromere antibodies in 26 patients, anti-U1-RNP antibodies in 5 patients, and anti-RNA polymerase III antibodies in 3 patient, respectively. The mean of mRSS was 6.3 points. The mean of RHI was 1.68, which was low as compared with healthy controls. In contrast, higher concentrations of PlGF, VEGF, GDF-15 and PTX-3 were found in SSc patients. The RHI inversely correlated with mRSS (r= -0.32, p<0.05). The significant high concentrations of PlGF, GDF-15 and PTX-3 were noted in diffuse type as compared with limited type. With regard to the analysis by coexistence of tissue damages, these biomarkers were also significantly higher in the tissue damages-positive group as compared with tissue damages-negative group (PlGF, GDF-15 and PTX-3 in digital ulcer-positive group, PlGF and GDF-15 in ILD-positive group). Conclusions: Low RHI and high circulating level of placenta growth factor, growth differentiation factor-15 and pentraxin-3 may reflect the presence of vasculopathy as well as progressive disease status in patients with SSc. References: Kawashiri SY, et al. Improvement of plasma endotheline-1 and nitric oxide in patients with systemic sclerosis by bosentan therapy. Rheumatol Int. in press. Disclosure of Interest: None declared DOI: 10.1136/annrheumdis-2014-eular.4200